Pediatric motor activity during sleep as measured by actigraphy. Issue 1 (17th October 2018) - Meltzer, Lisa J; Short, Michelle; Booster, Genery D; Gradisar, Michael; Marco, Christine A; Wolfson, Amy R; Carskadon, Mary A
Abstract: Study Objectives: Provide actigraphic reference values for motor activity during sleep for children and adolescents ages 8–17 years. Methods: Participants were 671 healthy community-dwelling children and adolescents (52% female, mean age 13.5 + 2.4 years) from the United States (64%) and Australia (36%). All participants wore an Ambulatory-Monitoring Inc. (AMI, Ardsley, NY) actigraph on their nondominant wrist for ≥5 nights and completed daily sleep diaries. Actigraphy data were scored with standard methods and a validated algorithm. Reference values were calculated for three outcome variables: percent sleep (sleep minutes/sleep period), mean activity count (average activity count over the sleep period), and restlessness measured by the activity index (% of epochs in sleep period > 0). Between-group differences were examined for sex and age group. In addition, changes to activity level across the sleep period were explored. Results: All participants had a minimum of three scorable nights of data, with 95% having at least five scorable nights. Reference values are presented by age group and sex, and reference percentiles are provided. Boys were found to have more activity in sleep across the three outcome variables. Age differences were also found for the three outcomes, but a consistent pattern was not detected across variables. Conclusions: This study is the first to examine motor activity from actigraphy in a large sample of healthy community-dwelling children and adolescents. Reference tables and percentiles, as well as sample actigrams highlighting different outcomes, are provided for clinicians and researchers who utilize actigraphy in pediatric populations.